Consensus statement on enzyme replacement therapy for mucopolysaccharidosis IVA in Central and South-Eastern European countries - Magner, Martin; Almássy, Zsuzsanna; Gucev, Zoran; Kieć-Wilk, Beata; Plaiasu, Vasilica; Tylki-Szymańska, Anna; Zafeiriou, Dimitrios; Zaganas, Ioannis; Lampe, Christina (Orphanet journal of rare diseases, 2022)
BACKGROUND: Mucopolysaccharidosis IVA (MPS IVA), or Morquio A syndrome, is a rare inherited metabolic disorder caused by deficiency of the lysosomal enzyme N-acetylgalactosamine-6-sulfatase. A progressive systemic skeletal chondrodysplasia, leading to significant morbidity and reduced life expectancy is the main clinical feature of this multisystemic disease. Although enzyme replacement therapy with elosulfase alfa is established in Europe, the rarity of disease and other factors still set hurdles in having patients treated in some countries. Aim of this statement is to provide evidence-based guidance for the enzyme replacement treatment of Morquio A patients, harmonizing recommendations from published guidelines with the real-life clinical practice in the Central and South-Eastern European region. PARTICIPANTS: The Consensus Group, convened by 8 Steering Committee (SC) members from 7 Central and South-Eastern European countries, consisted of a multidisciplinary group of 17 experts in the management of MPS in Central and South-Eastern Europe. CONSENSUS PROCESS: The SC met in a first virtual meeting with an external scientific coordinator, to discuss on clinical issues to be analyzed in guidance statements. Statements were developed by the scientific coordinator, evaluated by the SC members in a first modified-Delphi voting and adapted accordingly, to be submitted to the widest audience in the Consensus Conference. Following discussion and further modifications, all participants contributed to a second round of modified-Delphi voting. RESULTS: Nine of ten statements, concerning general guidelines for management of MPS IVA patients and specific recommendations for treatment, received final consensus. CONCLUSIONS: European guidelines and evidence-based recommendations for Morquio A patients should be considered in the real life of Central and South-Eastern European countries and adapted to unique clinical practice approaches and criteria for patients' access to treatment and reimbursement in the region.
Keywords: Morquio syndrome A; vrozené poruchy metabolismu aminokyselin; Consensus; Humans; Amino Acid Metabolism, Inborn Errors; Central and South-Eastern European countries; isovaleryl-CoA-dehydrogenasa; Mucopolysaccharidoses; lidé; Mucopolysaccharidosis IV; Mucopolysaccharidosis IVA; enzymová substituční terapie; konsensus; mukopolysacharidózy; Isovaleryl-CoA Dehydrogenase; mukopolysacharidóza IV; Enzyme Replacement Therapy; Elosulfase alfa; Enzyme replacement therapy